Design of Thermosensitive Niosomes by Eutectic Mixture of Natural Fatty Acids - Elisabetta Mazzotta; Martina Romeo; Zakaria Hafidi; Lourdes Perez; Ida Daniela Perrotta; Rita Muzzalupo (MDPI AG, 2024)
In the current study, a smart release system responsive to temperature was developed to improve the efficiency of tetracycline (TC) in antibacterial therapy. The nanovesicles designed consist of a non-ionic surfactant, SPAN60, cholesterol and a phase change material (PCM) as a thermoresponsive gating material. Niosomes were prepared using an increasing amount of PCM and characterized in terms of size, zeta potential, colloidal stability and thermoresponsive properties. The vesicles that developed were homogenous in size, had good biocompatibility and stability for up to 3 months and demonstrated thermoresponsive behavior. A low drug leakage was observed at 37 °C, while a rapid release occurred at 42 °C, due to the faster diffusion rate of the drug trough the melted PCM. This controllable drug release capacity allows us to avoid premature drug release, minimizing unwanted and toxic effects and ensuring a long retention time in the nanodevice so that it reaches the infected sites. In addition, TC-loaded niosomes were screened to investigate their antibacterial activity against various Gram-positive and Gram-negative bacteria by minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) assays. An interesting temperature-dependent antibacterial activity was observed against some bacterial strains: the niosomes activity against S. epidermis, for example, was improved by the temperature increase, as suggested by a reduction in MIC values from 112.81 to 14.10 μM observed at 37 and 42 °C, respectively. Taken together, the thermoresponsive platform developed allows us to use lower antibiotic amounts while ensuring therapeutic efficacy and, so, will advance the development of a novel antibacterial agent in clinical practice.